THE EFFECTIVENESS OF PRENATAL YOGA AS COMPLEMENTARY THERAPY ON BIRTH OUTCOMES - Kusumasari, Herdhika Ayu Retno (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Chilbirth may be a life-changing experience for women that can have an impact on them both emotionally and physically and leave them with lifelong memories. Preparing for childbirth from the beginning of pregnancy helps women manage their prenatal anxiety and produce healthy birth outcomes. The study literature is reviewed on databases from 2017-2023 of Science Direct, Cochrane Library, PubMed, and Google Scholar with inclusion and exclusion criteria. The result of analysis from 15 articles selected, it is concluded that prenatal yoga is significantly helping to shorten the labor duration in vaginal birth, lessen labor pain, decrease premature delivery, and significantly decrease the possibility of perineal tear, and improve the neonatal wellbeing.